Potential of Plant Essential Oils and Their Components in Animal Agriculture – in vitro Studies on Antibacterial Mode of Action - O’Bryan, Corliss A.; Pendleton, Sean J.; Crandall, Philip G.; Ricke, Steven C. (Frontiers in Veterinary Science, 2015)
The broad field of agriculture is currently undergoing major changes in practices, with new catch phrases including “organic” and “sustainable”. Consumers are more aware than ever before of the food that they eat and they want food free of toxic chemicals, antibiotics and the like. The antimicrobial activity of essential oils and their components has been recognized for several years. Recent research has demonstrated that many of these essential oils have beneficial effects for livestock, including reduction of foodborne pathogens in these animals. Essential oils as natural antimicrobials offer the opportunity to help maintain the safety of our food supply and minimize consumers’ concerns about consumption of synthetic chemicals. Numerous studies have been made into the mode of action of essential oils and the resulting elucidation of bacterial cell targets have contributed to new perspectives on countering antimicrobial resistance and pathogenicity of these bacteria. In this review, after a brief discussion of the uses essential oils in agriculture as antimicrobials, we give an overview of the current knowledge about the antibacterial mode of action of essential oils and their constituents as determined in vitro.